Modern aspects of diagnosis and treatment of patients with spontaneous coronary artery dissection - Sh. Sh. Zainobidinov; D. A. Khelimsky; A. A. Baranov; A. G. Badoyan; O. V. Krestyaninov (Кардиоваскулярная терапия и профилактика)
Spontaneous coronary artery dissection (SCAD) is one of the rarest causes of acute coronary syndrome. SCAD is most common in women <60 years of age (≥90% of cases) compared with men (10-12%). The rapid development of technologies used in interventional cardiology has made it possible to improve diagnostics and understand the pathogenesis. The management strategy in patients with SCAD is debatable and differs significantly from approaches to coronary atherosclerosis treatment. The review presents the results of recent studies. The angiographic classification of SCAD, the diagnostic algorithm and the choice of optimal treatment depending on clinical manifestations are also described.